2008
DOI: 10.1161/circresaha.108.171660
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Structural and Functional Consequences of the R33Q Homozygous Mutation in Cardiac Calsequestrin

Abstract: Abstract-Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited arrhythmogenic disordercharacterized by life threatening arrhythmias elicited by physical and emotional stress in young individuals. The recessive form of CPVT is associated with mutation in the cardiac calsequestrin gene (CASQ2). We engineered and characterized a homozygous CASQ2 R33Q/R33Q mouse model that closely mimics the clinical phenotype of CPVT patients. CASQ2R33Q/R33Q mice develop bidirectional VT on exposure to envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
121
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(140 citation statements)
references
References 26 publications
18
121
1
Order By: Relevance
“…The CSQ2 mutation knock-in mouse (9) was characterised in vitro and in vivo and was demonstrated to be an identical copy of the patient phenotype. CSQ2 and triadin protein levels were reduced, while the corresponding mRNAs levels remained unchanged (9). The CSQ2-R33Q protein levels found in this study confirmed the results of Rizzi and colleagues (9), who reported that CSQ2-R33Q proteins levels were significantly lower than wild-type protein levels.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The CSQ2 mutation knock-in mouse (9) was characterised in vitro and in vivo and was demonstrated to be an identical copy of the patient phenotype. CSQ2 and triadin protein levels were reduced, while the corresponding mRNAs levels remained unchanged (9). The CSQ2-R33Q protein levels found in this study confirmed the results of Rizzi and colleagues (9), who reported that CSQ2-R33Q proteins levels were significantly lower than wild-type protein levels.…”
Section: Discussionsupporting
confidence: 90%
“…CSQ2 and triadin protein levels were reduced, while the corresponding mRNAs levels remained unchanged (9). The CSQ2-R33Q protein levels found in this study confirmed the results of Rizzi and colleagues (9), who reported that CSQ2-R33Q proteins levels were significantly lower than wild-type protein levels. Comparison of the results reported in Figures 2A and 2B suggested that TD32 levels decreased due to the lack of functional CSQ2 from birth in the CSQ2-R33Q/R33Q mice.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…CASQ2 R33Q22 and knock out (KO)23 mice (3–6 months old, males) in the C57BL/6 genetic background were utilized in this study. All animal procedures were approved by The Ohio State University Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…The increase in [Ca 2+ ] i enhance the sarcoplasmic reticulum (SR) calcium load, exceeding the ryanodine receptor channel (RyR) threshold necessary to be opened and finally leading to spontaneous diastolic calcium release. The transient increase in citosolic Ca 2+ (waves) activates an inward (depolarizing) current (I ti ), mediated by the forward mode of NCX [99,100]. I ti is responsible for the generation of DADs which, when are sufficiently large to achieve the threshold, generate spontaneous CAP, leading to triggered activity [101].…”
Section: Role Of Nbc- Induced [Na+]i and [Ca2+]i Overload: Potential mentioning
confidence: 99%